Knowledge of the general physicians on surgical ethics especially on informed consent among surgically emergency patients in Chittagong Medical College Hospital, Bangladesh - Faruquzzaman, M; Akter, Seikh Farid Uddin; Mazumder, Saroj Kumar; Hasan, Suzon Al; Hassan, Md Mahtab Uddin (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v19i2.3868 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):33-38